Pemetaan Kepentingan dan Relasi Stakeholder dalam Pengembangan Wisata Kebun Rojo Camp Kabupaten Malang - Hidayatul Ana Bella; Imarotul Mahbubah; Mauliya Safira; Muh. Rifqi Ramadhan; Nisa Diah Silvana; Noor Safina Wahyuni (Jurnal Abdimas Pariwisata, 2024)
Mapping of Interests and Stakeholder Relations in the Development of Rojo Camp Garden Tourism in Malang Regency. This study aims to determine the mapping of interests and stakeholder relations in the development of Rojo Camp Garden tourism. This study uses a descriptive research method with a qualitative approach to be able to describe in detail and depth how the mapping and stakeholder relations in the development of Rojo Camp Garden tourism. Data collection techniques used are field observations, in-depth interviews, and documentation. Then this study uses Structural theory by Anthony Giddens because it is suitable in an effort to map actors and relationships and what is the interest of these actors. It can be concluded that the results of the research are that the Rojo Garden located in Gadingkulon Village, Dau District, Malang Regency was built by the local community with the aim of empowering themselves and providing jobs for the lower class or needy people around the location. Even though Rojo Gardens is still not registered as an official business at the FMU, the management hopes that with the help of students, the licensing process will soon be completed and Rojo Gardens can be officially established. The management does not want to work with outsiders or investors because of bad experiences when working with investors in the management of Coban Parang Tejo.